The Relationship of the Old Testament Prophets with Civil Authorities from the perspective of Human Rights: The Case of Naboth’s Vineyard (1 Kgs 21: 1-16) - Varga, Cătălin ca. 20./21. Jh. (Diakrisis, 2019)
The present study aims to analyze from a different point of view the already established message, the theological message behind the episode "Naboth’s Vineyard". For this, we propose to look strictly from the perspective of Old Testament culture, the relationship between the prophet of God and the representative of civil authority, insisting on the particularity of human rights (as they were left by God in the Torah). We pay close attention to whether they are widely respected, and if not, we try to identify the moment when their violation occurs and the synchronic reasons behind the delegitimization actions of the concept. The case of Naboth’s vineyard is taken as a case study, in which we highlight the corrupt games of the corrupt king Ahab, which facilitated the dispossession of the parental legacy and finally the murder of the grape grower Nabot. At the same time, we strengthen the indisputable need of the prophet, who is stepping forward, ready to face the cost of life, corruption and monarchical immorality, in order to rebalance the social balance of Israel.